The Influence of Emotional Intelligence and Job Stress on Job Satisfaction and Their Impact on Employee Performance - Monica Poetrie, Anandra; Handaru, Agung Wahyu; Ahmad, Gatot Nazir (Politeknik Siber Cerdika Internasional, 2023)
The rapid and increasingly intense economic competition has driven companies from various sectors, including the banking sector, to actively compete in providing the best services and adopting the latest technologies. This is closely related to the utilization of available resources, one of which is human resources. The role of human resource management is crucial for the sustainability of an organization, influencing organizational performance, strategy implementation, and the achievement of established goals. Human resources become a primary factor in driving companies towards achieving high performance. Performance serves as an indicator of how well actions or policies can attain the company's goals and manifest the vision and mission of the organization. This concept is grounded in the strategic planning of the organization or company. This study employs a quantitative approach and aims to investigate the level of job satisfaction and its impact on employee performance as an intervening variable. Participants in this study are employees working at PT X, with a total sample size of 105 respondents. Data analysis is conducted using SPSS and Smart PLS version 3 software. The findings from this research demonstrate noteworthy effects: emotional intelligence holds a notable impact on job satisfaction, emotional intelligence significantly affects employee performance, job-related stress significantly influences job satisfaction, work-related stress significantly impacts employee performance, and job satisfaction significantly affects employee performance.